Human T-cell leukemia virus type 1 is associated with dysthyroidism in the French Amazon - Dugardin, Julia; Demar, Magalie; Hafsi, Nezha; Amroun, Hakim; Aurelus, Jean-Markens; Drak Alsibai, Kinan; Ntoutoum, André; Santa, Florin; Nacher, Mathieu; Sabbah, Nadia (Frontiers in Cellular and Infection Microbiology, 2023)
Background Human T-cell leukemia virus type 1 (HTLV-1) is a retrovirus known to cause two major diseases: adult T-cell leukemia/lymphoma and a progressive neuromyelopathy—tropical spastic paraparesis. Many viruses may be involved in the pathogenesis of thyroiditis; however, few studies have focused on the role of HTLV-1. We aimed to investigate the association between HTLV-1 and biological thyroid dysfunction. Methods We included 357 patients with a positive HTLV-1 serology and thyroid-stimulating hormone assay data between 2012 and 2021 in a hospital in French Guiana; we compared the prevalence of hypothyroidism and hyperthyroidism in this group with that in an HTLV-1-negative control group (722 persons) matched for sex and age. Results The prevalence of hypothyroidism and hyperthyroidism in patients with HTLV-1 infection was significantly higher than that in the control group (11% versus 3.2% and 11.3% versus 2.3%, respectively; p < 0.001). Conclusion Our study shows, for the first time, the association between HTLV-1 and dysthyroidism in a large sample, suggesting that thyroid function exploration should be systematically implemented in this population as this may have an impact on therapeutic management.